Pengaruh Good Corporate Governance terhadap Manajemen Laba (Studi Kasus pada Sektor Property dan Real Estate yang Terdaftar di BEI Periode Tahun 2017-2021) - Dede Hertina; Nuri Nuryanah (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of the research is to analyze the effect of Good Corporate Governance on Earnings Management. Good Corporate Governance. in this research measured using Institutional Ownership, Managerial Ownership, and Independent Board of Commisioners. The analytical method used in this study is quantitative method with the population of this study, are property and Real Estate companies listed on the Stock Exchange period 2017-2021 were selected using purposive sampling and the number of samples obtained 14 companies with the research period 5 year. The data analysis used in this study is panel data regression. the result showed that Institutional Ownership and Independent Board of Commisioners did not give significant influence the Earnings Management, by contrast Managerial Ownership did influence the Earnings Management.